PRESENTATION AND PREDISPOSING FACTORS OF NUTRITIONAL RICKETS IN CHILDREN OF HAZARA DIVISION - Siddiqui, Tahir Saeed; Rai, Manzoor Illahi (Journal of Ayub Medical College Abbottabad, 2005)
Background: There is no local data about rickets available in Hazara Division, while clinical experience suggests that problem exists in this area with abundant sunlight. We carried out this study with an objective to determine presence, presentation and predisposing factors of rickets in pediatrics population of Hazara Division. Methods: This study was conducted in Department of Pediatrics, Ayub Teaching Hospital Abbottabad over a twelve months period from July 2003 to July 2004. Children from newborns to fifteen years of age presenting with signs and symptoms of rickets were included and information regarding signs, symptoms, predisposing factors (crowded housing, isolated housing with deficient sun exposure, abundant sun but lack of awareness, malnutrition and antenatal factors) and investigations was recorded on a proforma. Diagnosis was based on clinical signs, radiological changes on x-ray wrist joint and biochemical disturbances in serum levels of alkaline phosphatase, calcium, and inorganic phosphorus. Results: Sixty Children with rickets reported during the study period. The main clinical presentation was in the form of delayed motor milestones in 20 (33.33%) children, recurrent lower respiratory infections in 11 (18.33%) children, recurrent diarrhea in 12 (20%) children, and fits in 3 (5%) children. Skeletal changes on clinical examination were present in 40 (66.6%) children. Radiological signs of rickets were present in 51 (85%) children. Symptoms and signs reverted to normal in all cases after vitamin D supplementation. The apparent risk factors were lack of awareness, malnourishment and antenatal factors. Conclusion: Rickets is common in Hazara Division presenting with variable signs and symptoms, predisposing the childhood population to different illnesses and skeletal deformities. In the presence of abundant sunshine lack of awareness of exposure to sun, malnutrition and antenatal factors may be the important predisposing factors for development of nutritional rickets. Key words: Rickets, vitamin D deficiency, and malnutrition.